AMERICAN POLICY IN CENTRAL ASIA AND RUSSIA’S INTERESTS - BRATERSKIY, Maxim (CENTRAL ASIA AND THE CAUCASUS, 2007)
Five years ago, I published an article1 in which I assessed the results of the first decade of America’s Central Asian policy. I came to the conclusion that between the early 1990s and 2002, it developed from mere recognition of the newly independent states to a long-term regional strategy. For obvious reasons, 9/11 served as the turning point: “From a geographically remote, un-stable and, in general, unexciting region, Central Asia became a zone of the U.S.’s national security interests.”2 After the 9/11 events, America began launching a wide-scale counterterrorist campaign in Asia. In the wake of 11 September, when the United States began its military operation in Afghanistan and set up military bases in Central Asia, the American military and politicians worked against the clock. Tactics, not strategy, was on everyone’s mind. The prospect of America’s regional involvement was still vague.t was later, in the mid-2000s, that America’s interests in the region were soberly assessed both in America and Russia. Today, when America, Russia, and China have outlined their interests in Central Asia in the context of its relative stability and when regional structures have appeared with good prospects (in particular the SCO), we can return to the problem of America’s policy in Central Asia and its prospects. The time has come to give a more objective and balanced assessment,to ascertain whether Central Asia remains high on the list of the U.S. foreign policy priorities, and to outline Russia’s response to America’s regional policy. Today, three interconnected factors are re-sponsible for the U.S.’s interest in Central Asia:its geopolitical status.the insufficient political and economic stability of the local states and the hu-man rights problems caused by regional instability; andthe prospect of transferring the local hydrocarbon resources to the world market. Since the United States is pursuing its Central Asian policy in the context of much wider regional and global problems, an analysis of what America is doing in Central Asia should take into account the Iranian nuclear program, the positions and roles of India and Pakistan, and SCO development.